British crime survey, 2007-2008: unrestricted access teaching dataset (Crime Survey for England and Wales, 2011)
The British Crime Survey 2007-2008: Unrestricted Access Teaching Dataset is based on the British Crime Survey, 2007-2008 (available from the UK Data Archive under SN 6066) and constitutes real data which are used by the Home Office and are behind many media headlines. The teaching dataset is a subset which has been subjected to certain simplifications and additions for the purpose of learning and teaching. (Note that the main British Crime Survey has now become the Crime Survey for England and Wales, but titles of older studies in the series remain the same.) The main differences are: only respondents who completed Module B (attitudes to the Criminal Justice System) of the BCS, 2007-2008 are included, the number of variables has been reduced weighting has been simplified, a reduced codebook is provided additional continuous variables have been created (using factor analysis of pre-existing variables) in order to facilitate their use in quantitative methods classes. Further information is available in the study documentation (below) which includes a dataset user guide and additional notes for teachers. Differences between the unrestricted dataset and the standard access BCS teaching dataset: Note that SN 6561, the British Crime Survey 2007-2008: Teaching Dataset contains a larger subset of BCS 2007-2008 variables than the unrestricted version, and is only available to registered users of the UK Data Service.